Formulation, Development and Testing of Enhanced Biofertilizer on Vegetable Garden - Afiqah Farzana, Mahdi (Universiti Malaysia Sarawak (UNIMAS), 2017)
A research was carried out in order to formulate, develop an enhanced biofertilizer and testing it on vegetable garden (Bok Choy). The preparation on biofertilizer was conducted in the Molecular Genetic Laboratory and Soil Science Laboratory, Universiti Malaysia Sarawak (UNIMAS). The pot trial was conducted using Bok Choy. This research study used 3 bacteria treatment for formulating biofertilizer; Bacillus amylo, Bacillus cereus, Enterobacter. Parameter such as height of plant, length of leaves, root and shoot ratio, dry and fresh weight were obtained. The data was collected during 19 week period. From this study showed, Bok Choy planted in a mixture of OPEFB (oil palm empty fruit bunch) compost, top soil, and fine sand inoculated with 10% of each treatment (Bacillus amylo, Bacillus cereus, Enterobacter).